Differences in Physical Activity, Lactic Acid Concentration, and Quality of Life between Gender among First Year Medical Students - Rachmawati, Maria Regina; Sidarta, Nuryani; Mediana, Dian (Majalah Kedokteran Bandung, 2019)
Medical students have fewer opportunities to do physical activities (PA) that may increase the risk for chronic diseases. The aim of this study was to assess the correlation between PA, as assessed using the International Physical Activity Questionnaire (IPAQ), and Lactic acid (LA) concentration, as well as the differences in IPAQ, LA, and quality of life (QoL) between genders. This was a cross-sectional study conducted in April - November 2017 by a private university in West Jakarta. Subjects of the study were selected using simple random sampling approach with female subjects as the more dominant gender ( n=76, 60%) from the 126 subjects recruited. The median of IPAQ, La- 1, and La-2 in male and female were 707 (474–944) vs 423 (392–501) Mets (p=0.7), 4.6 (3.8–5.4) vs 2.8 (2–3) mmol/L (p=0.001), and 8.4 (7.7–8.9) vs 10 (9.3-10.5) mmol/L (p<0.001) respectively. The higher the IPAQ, the lower of the La- 2 concentration (p=0.012) was when analyzed using Kruskal-Wallis test. Total score of QoL in males and females were 2628.6 (2,496-2757) and 2,765 (2,687–2,859) (p=0.067), respectively, while the concepts of Role Limitation due to Physical Health was higher in female (p=0.006), as shown by Mann-Whitney test. In conclusion, subjects arephysically inactive with females are less active and have a higher La-2 concentration than males. However, the QoL concept of the RLPH is better in female students. Perbedaan Aktivitas Fisik, Asam Laktat, dan Kualitas Hidup antara Jenis Kelamin pada Mahasiswa Kedokteran Tahun Pertama Mahasiswa Fakultas Kedokteran memiliki sedikit kesempatan untuk melakukan aktivitas fisik yang dapat meningkatkan terjadi penyakit kronis. Tujuan penelitian menemukan korelasi aktivitas fisik (PA) yang dinilai menggunakan the International Physical Activity Questionnaire (IPAQ) dengan kadar asam laktat (LA), serta perbedaan IPAQ, LA dan kualitas hidup (QoL) antar jenis kelamin. Desain penelitian adalah potong lintang, seleksi subjek secara acak sederhana, pada April–November 2017, pada universitas swasta di Jakarta Barat. Hasil penelitian diperoleh 126 subjek, 76 (60%) perempuan. Rerata IPAQ, LA -1, dan LA -2 pada laki-laki dan perempuan secara berurutan adalah; 707(474–944) vs 423 (392–501) Mets (p=0,7), 4,6 (3,8–5,4) vs 2,8 (2–3) mmol/L (p=0,001), dan 8,4 (7,7–8,9) vs 10 (9,3-10.5) mmol/L (p<0,001). Semakin tinggi IPAQ, semakin rendah LA (p=0,012), dengan Uji Kruskal-Wallis. Skor total QoL pada pria dan wanita adalah 2.628.6 (2496–2.757) vs 2.765 (2.687–2.859) (p=0,067), sementara nilai konsep Role Limitation due to Physical Health (RLPH) pada perempuan lebih tinggi (p=0,006) dengan Uji Mann-Whitney. Kesimpulan, subjek memiliki PA tidak aktif, sementara perempuan lebih tidak aktif dan memiliki LA-2 lebih tinggi. Namun, QoL pada konsep RLPH lebih baik pada mahasiswa perempuan.